UK: The Concurrent Enforcement by Regulators of Competition Law and Sector-Specific Regulation. (22nd July 2016) - Graham, Cosmo
Abstract: The UK has a unique model where competition law is enforced concurrently by the Competition and Markets Authority (CMA) and the sector regulators. A major reform was implemented by the Enterprise and Regulatory Reform Act 2013, extending concurrent powers to the financial services sector and the National Health Service. The reform led to more enforcement activity as well as to greater contacts, seemingly more information flows, greater understanding, and perhaps more trust between the agencies.